Legal Liability Of Ppat Due To Legally Defective Land Sale And Purchase Deed (Study of Supreme Court Decision No. 3507 K/Pdt/2023) - Tinrif Valins Dongoran; Roida Nababan; Sovia Febrina Tamaulina Simamora (PALAR | PAKUAN LAW REVIEW, 2026)
Abstract Land is an important resource for human life, so the transfer of land rights must be Land is an essential resource for human life; therefore, the transfer of land rights must be carried out in accordance with legal provisions to ensure legal certainty and protection. The Land Deed Official (PPAT) has a strategic role in drafting deeds of transfer of land rights, particularly deeds of sale and purchase, which must fulfill the formal and material requirements as stipulated in statutory regulations. This study aims to examine the implementation of the transfer of certified land rights as regulated by law and to analyze the legal responsibility of the PPAT for a land sale and purchase deed declared legally defective based on Supreme Court Decision Number 3507 K/Pdt/2023. The method used in this research is normative juridical, employing statutory, conceptual, and case study approaches. Data were obtained through library research on primary, secondary, and tertiary legal materials and were analyzed qualitatively using legal reasoning. The results of the study indicate that a PPAT bears legal responsibility if negligent in carrying out the pre-deed, deed-making, and post-deed procedures, resulting in the sale and purchase deed losing its legal validity. Such responsibility includes civil liability, administrative liability, and professional ethical responsibility. The Supreme Court decision emphasizes that drafting a deed without the consent of the lawful landowner constitutes an unlawful act and renders the deed null and void by law. Therefore, compliance by the PPAT with legal procedures is a key factor in ensuring legal certainty and the protection of land rights. Keywords: Transfer of Land Rights, Legal Responsibility, Unlawful Act